Rare intraspinal clear cell meningioma in children: a case report and literature review. Issue 10 (October 2020) - Hao, Zheng; Hu, Si; Yu, Nian-Zu
Meningioma of the spinal canal is very rare. Clear cell meningioma (CCM) with special histological features occurs more commonly in the spinal cord. A review of the published English-language literature identified 40 reported cases of children with intraspinal CCM and this current report presents an additional case of a 3-year-old child with confirmed lumbar CCM. The current case underwent gross total resection of the CCM. At 9 months after the operation, lumbar magnetic resonance imaging was undertaken and confirmed the absence of tumour recurrence. The child was able to walk normally again. During this period, the child did not receive adjuvant treatments such as radiotherapy and chemotherapy. An evaluation of the 41 cases demonstrated the following: (i) there was no significant difference between the recurrence rate of females and males; (ii) there was a significant difference in the recurrence rate based on the extent of resection (gross total resection versus partial resection); (iii) the recurrence rate in patients where the number of involved segments ≥3 levels was significantly higher than that in patients where the number of involved segments was 1–2 levels. For children with CCM, complete surgical resection might be an important characteristic for predicting the risk of the recurrence of CCM.